Uso de viscum album no ponto de acupuntura VG14 como terapia adjuvante à mastectomia radical em cadelas com neoplasias mamárias - Figueiredo, Renata Nogueira [UNESP] (2014)
Acupuncture should be seen as an adjuvant treatment modality, because it improves the quality of life of patients with cancer, in addition to controlling these metabolic changes. Concomitantly, Viscum album extract used in anthroposophical medicine can be used to cause cytotoxicity and apoptosis of tumor cells and therefore has been widely applied. The data showed an increase of these effects when applied at point Governor Vessel. (VG14), one of the immunity points. For decades numerous therapies have been used to combat cancer, wherein the surgery still is the primary form of treatment protocols which are set according to the type and place of occurrence thereof. Other therapies are also applied as chemotherapy employing cytotoxic agents, but they produce side effects and adverse effects. We conclude that adjuvant therapy made the bitches presented lower values of globulins, calcium and FA to assist in preventing the development of paraneoplastic syndromes. However, further research should be conducted to more accurately assess the beneficial effects of using these complementary therapies, as this chapter shows